Preventing Violence in the Most Violent Contexts : Behavioral and Neurophysiological Evidence - Dinarte, Lelys (World Bank, Washington, DC, 2019)
This paper provides experimental evidence of the impact of an after-school program on vulnerable public-school students in El Salvador. The program combined a behavioral intervention with ludic activities for students aged 10-16 years old. The authors hypothesize that it affects violence, misbehaviors, and academic outcomes by modulating emotional regulation or automatic reactions to external stimuli. Results indicate the program reduced reports of bad behavior and school absenteeism while increasing students’ grades. Neurophysiological results suggest that the impacts on behavior and academic performance are driven by the positive effects of the program on emotional regulation. Finally, the study finds positive spillover effects for untreated children.